Roadmap and recommendations - organizing of a study tour in Europe for Caribbean business people from the cultural industries; presented by ACE, International Consultants, Spain - Mora, Taiana (EU BrusselsBE, 2012)
Aims to develop a roadmap for the development of the cultural and creative industries in CARIFORUM which would identify the key areas of intervention.